2010
DOI: 10.1108/17465261011045133
|View full text |Cite
|
Sign up to set email alerts
|

HR function developments in Lithuania

Abstract: PurposeThe purpose of this paper is to provide an overview of past and current developments in human resource (HR) function in Lithuania.Design/methodology/approachThe paper discusses the antecedents of HR function developments in Lithuania through an analysis of the country's demographic, economic, legal and cultural environments and historical human resource management (HRM) developments. Current HR function status is shown through findings of an HR manager/specialist survey conducted at 119 medium‐ and larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
7
0
3
Order By: Relevance
“…As noted for collectivism, extant research indicates differences in the effectiveness of HR practices according to power distance levels. For example, processes such as 360° feedback or general employee feedback are less appealing or effective in high power distance societies, because by nature, these methods require more participation across hierarchal levels (Davis, 1998; Fletcher & Perry, 2001; Kazlauskaite & Buciuniene, 2010; Ollo-López, Bayo-Moriones, & Larraza-Kintana, 2011; Sartorius, Merino, & Carmichael, 2011; Zhang & Begley, 2011; Singh, Mohamed, & Darwish, 2013; Chen, Zhang, & Wang, 2014; Jiang, Colakoglu, Lepak, Blasi, & Kruse, 2014), seeking feedback from subordinates may appear to undermine a supervisor’s authority (Gregersen, Hite, & Black, 1996; Silva, Roque, & Caetano, 2015), and appeal processes may seem unsuitable because they challenge authority (Fletcher & Perry, 2001). Power distance also influences the design of training (Wang, Wang, Ruona, & Rojewski, 2005; Festing & Barzantny, 2008; Fu & Kamenou, 2011; Ollo-López, Bayo-Moriones, & Larraza-Kintana, 2011), compensation, appraisals (Schuler & Rogovsky, 1998; Chow, Lo, Sha, & Hong, 2006; Singh, Mohamed, & Darwish, 2013; Festing & Knappert, 2014), communication (Chen, Zhang, & Wang, 2014; Yang, Zhou, & Zhang, 2015), and career development (Aycan & Fikret-Pasa, 2003; Chow, Lo, Sha, & Hong, 2006; Festing & Barzantny, 2008; Fu & Kamenou, 2011) initiatives.…”
Section: Globe Cross-cultural Studies and Management Practicesmentioning
confidence: 99%
“…As noted for collectivism, extant research indicates differences in the effectiveness of HR practices according to power distance levels. For example, processes such as 360° feedback or general employee feedback are less appealing or effective in high power distance societies, because by nature, these methods require more participation across hierarchal levels (Davis, 1998; Fletcher & Perry, 2001; Kazlauskaite & Buciuniene, 2010; Ollo-López, Bayo-Moriones, & Larraza-Kintana, 2011; Sartorius, Merino, & Carmichael, 2011; Zhang & Begley, 2011; Singh, Mohamed, & Darwish, 2013; Chen, Zhang, & Wang, 2014; Jiang, Colakoglu, Lepak, Blasi, & Kruse, 2014), seeking feedback from subordinates may appear to undermine a supervisor’s authority (Gregersen, Hite, & Black, 1996; Silva, Roque, & Caetano, 2015), and appeal processes may seem unsuitable because they challenge authority (Fletcher & Perry, 2001). Power distance also influences the design of training (Wang, Wang, Ruona, & Rojewski, 2005; Festing & Barzantny, 2008; Fu & Kamenou, 2011; Ollo-López, Bayo-Moriones, & Larraza-Kintana, 2011), compensation, appraisals (Schuler & Rogovsky, 1998; Chow, Lo, Sha, & Hong, 2006; Singh, Mohamed, & Darwish, 2013; Festing & Knappert, 2014), communication (Chen, Zhang, & Wang, 2014; Yang, Zhou, & Zhang, 2015), and career development (Aycan & Fikret-Pasa, 2003; Chow, Lo, Sha, & Hong, 2006; Festing & Barzantny, 2008; Fu & Kamenou, 2011) initiatives.…”
Section: Globe Cross-cultural Studies and Management Practicesmentioning
confidence: 99%
“…But the research done in Lithuania reveals that corporate social responsibility faces serious difficulties. For example, R. Kazlauskaitė andI. Bučiūnienė (2010: 2018) have shown that almost half of all companies had instituted some policies of social responsibility, but only a few of them took action that was not prescribed by law.…”
Section: Research Of Workplace Relations In Lithuaniamentioning
confidence: 99%
“…The research of changes in the function of human resource specialists in Lithuanian organisations (Bakanauskienė et al, 2008;Jagminas et al, 2009;Kazlauskaitė et al, 2010;Lobanova, 2009, etc. ) reveals that tensions in the labour market influenced a significant growth of the functions of human resource specialists in areas such as the recruitment and selection of employees, labour security, followed by induction, appraisal, and employee training; a significant growth awaits such functions as administering the payroll, strategic planning and administration, the development of teamwork skills, projection of the organisation, and change management.…”
Section: Changes In the Functions And Competences Of Human Resource Smentioning
confidence: 99%